Identifikasi Kualitas/Keberfungsian Sarana dan Prasarana pada Rusunawa Lampulo, Kota Banda Aceh - Cut Yusra; Irin Caisarina; Hilda Mufiaty; Farisa Sabila (Universitas Syiah Kuala, 2023)
Flats are one of the solutions of increasing community growth for residential housing which poses a challenge to the limited housing area. which have several halls and infrastructure. However, the decline in the quality and function of facilities and infrastructure of the flats cannot be avoided. This study aims to determine the quality of the facilities and infrastructure in Lampulo Rusunawa by using a qualitative descriptive approach. Data collection was carried out by observation, interviews, documentation and conducting related literature studies. The results of the study indicate that some of the available facilities cannot be used properly and the community has been looking for adjustments and alternatives to these problems. It needs special attention from the management on the qualities and malfunctions of the facilities and infrastructure of the flats. It is hoped that this Lampulo rusunawa can be used as an evaluation material as stated in SNI 03-1733-2004, which is developed in an integrated, directed, planned, and sustainable manner to increase community growth for residential housing